Do foreign asset holdings affect household consumption? - Cameron McLoughlin (Graduate Institute of International and Development Studies, 2010)
Scant attention has been paid in the literature concerning 'consumption wealth effects' to asset heterogeneity in terms of foreign and domestic asset holdings. Through extending the approach of Lettau and Ludvigson (2004).and Nitschka (2007), this study uncovers that whilst households tend to view innovations to domestic asset holdings as part of their permanent income, changes in the value of foreign equity holdings are largely characterised as temporary in nature and unrelated to household consumption decisions. This evidence complements existing work concerning 'valuation effects' by highlighting at a disaggregated level an important mechanism by which this phenomenon affects a fundamental macroeconomic aggregate, and also draws implications for trade balance outcomes.
Keywords: F41; F39; 330; Valuation Effects; Household Consumption; Cointegration; Kapitalanlage; Privater Haushalt; Verbraucherausgaben; Kointegration; Schätzung; USA